Livelihood Diversification and Household Resilience among Seaweed Farmers in South Sulawesi: Evidence from the Kuda Laut Farmer Group, Bulukumba - Hidayat Nur Ababil Hidayat; Nadir; Muh. Ikmal Saleh; Sri Mardiyati; Saleh Molla (Tarjih : Agribusiness Development Journal, 2026)
This study aims to identify the forms of livelihood strategies and household livelihood patterns of the Kuda Laut Farmer Group in Sapolohe Village, Bontobahari District, Bulukumba Regency. The study employed a qualitative approach with a snowball sampling technique involving 10 members of the farmer group as informants. Data were collected through in-depth interviews, observation, and documentation, and were analyzed through data reduction, data display, and conclusion drawing. The results show that seaweed-farming households apply multiple livelihood strategies consisting of on-farm, off-farm, and non-farm strategies. The on-farm strategy is carried out through seaweed cultivation as the main source of income and capture fishing as an additional occupation. The off-farm strategy includes collecting seaweed and providing transportation services for fishery products, while the non-farm strategy includes construction labor, grocery stalls, phone-credit kiosks, and BRI link services. The sustainability of these strategies is supported by livelihood assets consisting of natural, human, physical, social, and financial capital. Social capital in the form of mutual cooperation and human capital in the form of family labor are the most prominent supporting factors. Household livelihood patterns tend to take the form of multiple livelihoods strengthened by job diversification, the use of family labor, and the migration of family members. This study recommends strengthening group legality, access to capital, and post-harvest training to increase the added value of seaweed.